Eco-Friendly Indigenous Farming Practices among Sorsoguenos in Sorsogon, Philippines - Ocbian, Magdalena; Lasim, Maria (JPAIR Multidisciplinary Research, 2015)
Indigenous practices are part of people’s life and culture. In Sorsogon province, Philippines, numerous indigenous practices are observed, but only few are documented. This study delved specifically on documenting the eco-friendly indigenous farming practices on seed preservation and storage, land preparation, fertilization, crop protection and organic farming. This descriptive research utilized surveys, interviews, and observation. Respondents are farmers with ages 55 to 75 coming from rural communities in Sorsogon province. Among the ecofriendly practices on seed preservation and storage include placing unthreshed seeds above wood-burning stoves or hanging them in smoky areas of the kitchen until the next planting season. Rice are preserved by air-drying and mixing them with leaves like kilala, alagao (Premna odorata), lagundi (Vitex negundo), or charcoal. Spraying with achuete (Biya orellana) leaf extract or powdered fruits of siling labuyo (Capsicum frutescens) is also practiced. To protect crops from insect infestation, farmers collect, grind and spread rice bugs in the field to make the soil fertile. Dead animals are buried near the tree. These gathered alternative farming practices could contribute to the global concern of mitigating climate change. However, with the influx of modern technology, these practices may be forgotten if not documented and advocated.
Keywords: Social Science; indigenous knowledge system (IKS); Indigenous farming practices; seed conservation; Sorsogon Province; Philippines